FARM DEBT AND INVESTMENT. EMPIRICAL EVIDENCE FROM BULGARIAN AGRICULTURE - Desislava IVANOVA; Evgeni GENCHEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article explores the relationship between farmers' investment activity and debt structure in order to bring out the factors mediating the outcome. Overleveraging is one of the most serious problems faced by the Bulgarian farmers due to the high levels of competition in the EU. This research is based on a stratified random sample of 5% (2,985 observations) on farms in the agricultural sector encompassing the sub-sectors crop production, livestock production and auxiliary activities, with a research horizon of five years. A fixed-effect panel threshold regression analysis is used. The obtained results show that where the debt level is high, this has a negative impact on the investment activity of the farms in the agriculture sector.